Аdaptive teaching of the bilingual students at higher school institution - N. SH. Miftakhova; V. G. Ivanov (Высшее образование в России)
The foundations for formation of the pedagogical system of adaptive teaching of students on a bilingual basis at a technological institute of a chemical profile is presented in this paper. There are described the pedagogical approaches, didactic principles, psychological and pedagogic factors forming the basis of adaptive teaching of first-year students among ethnicyouth.